Massive gastrointestinal bleeding due to ectopic varix in distal duodenum: a case report. Issue 3 (4th May 2021) - Mallea, Patrick; Allen, Aaron; Lynch, Maureen Kim; Jensen-Otsu, Elsbeth; Tompkins, David
ABSTRACT: Duodenal ectopic varices (DEV) are an uncommon etiology of upper gastrointestinal bleeding and are associated with high mortality. Both the diagnosis and management of DEV are challenging. Multiple treatment modalities exist including endoscopic guided management (ligation and sclerotherapy), surgical resection, transvenous obliteration and transjugular intrahepatic portosystemic shunt (TIPS), but management depends on the underlying vascular anatomy and underlying pathology. We present a case of a 41-year-old man with a history of an alcohol use disorder, prior splenic vein thrombosis as a complication of pancreatitis who presented with massive gastrointestinal bleeding, and was ultimately diagnosed with distal duodenal ectopic varix, which contained inflow from a medial branch of the superior mesenteric vein and outflow into the left renal vein. He was successfully treated with transjugular portosystemic shunt and coil embolization.